An Analysis of the Xiaomi Phones Sell Well Around the World - Wang, Qi (Journal of Education, Humanities and Social Sciences, 2025)
With the development of the mobile Internet, domestic smartphone companies have joined the battle for market share in recent years. The competition in the domestic market is getting more and more intense, with the diversification of consumer demand and the continuous improvement of consumption levels. In recent years, as a newcomer Xiaomi mobile phones naturally pulled the country's vision to the domestic mobile phones, but also set off a wave of ‘Xiaomi fever’. At this time, the product characteristics of Xiaomi mobile phones have also attracted the attention of industry leaders. This study analyses the reasons for the popularity of Xiaomi mobile phones on the basis of the basic information about Xiaomi mobile phones and gives an outlook on the development prospects of Xiaomi mobile phones. This paper provides a comprehensive analysis of Xiaomi's pricing strategy, business model, and differentiation strategy. At the same time, this paper also puts forward reasonable suggestions for Xiaomi's future development based on the current market situation. The author hopes that these suggestions can help enterprises improve their overall strength, and withstand the rapid development of this era of the torrent, in the fierce competition to survive.